2023
DOI: 10.1097/md.0000000000034605
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection increases the risk of nonalcoholic fatty liver disease: Possible relationship from an updated meta-analysis

Chenchen Liu,
Qian Wu,
Ranran Ren
et al.

Abstract: Background: The relationship between Helicobacter pylori (H pylori) infection and nonalcoholic fatty liver disease (NAFLD) has long been debated. Although it has been investigated in many observational studies, the results remain controversial. Therefore, we performed an updated meta-analysis to assess the association between H pylori infection and risk of NAFLD by collecting relevant articles. Methods: Literature collections were conducted by searching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…From 2018 to 2022, some systematic reviews and meta-analyses with fewer observational studies included [61][62][63][64][65] have been undertaken. In 2023, Liu et al 66 meta-analysing 28 studies (24 cross-sectional, 2 case-control, and 2 cohort studies altogether) reported that H. pylori infection was associated with a mildly increased risk of MASLD (pooled OR 1.27; 95%CI 1.18-1.38), although a highly significant heterogeneity was observed (I 2 = 89.7%). More recently, Xu et al 67 performed a meta-analysis of 27 cross-sectional studies, 3 case-control studies, and 4 cohort studies.…”
Section: Weightmentioning
confidence: 99%
“…From 2018 to 2022, some systematic reviews and meta-analyses with fewer observational studies included [61][62][63][64][65] have been undertaken. In 2023, Liu et al 66 meta-analysing 28 studies (24 cross-sectional, 2 case-control, and 2 cohort studies altogether) reported that H. pylori infection was associated with a mildly increased risk of MASLD (pooled OR 1.27; 95%CI 1.18-1.38), although a highly significant heterogeneity was observed (I 2 = 89.7%). More recently, Xu et al 67 performed a meta-analysis of 27 cross-sectional studies, 3 case-control studies, and 4 cohort studies.…”
Section: Weightmentioning
confidence: 99%